b - Small, Marian (b, 2020)
"Now in its Fourth Edition-with more than 50 new questions and a new chapter on financial literacy-this bestselling resource helps experienced and novice teachers to effectively and efficiently differentiate mathematics instruction in grades K-8. Math education expert Marian Small shows teachers how to get started and become expert at using two powerful and universal strategies: Open Questions and Parallel Tasks. This edition is even easier for teachers to use in all quality state standards environments, including direct links to content standards and standards for mathematical practice. Parallel tasks and question examples are provided at each grade band: K-2, 3-5, and 6-8. Along with each example, the text describes how teachers can evoke productive conversations that meet the needs of a broad range of learners. Book Features: New tasks and questions to develop Financial Literacy. Connection of tasks and questions to standards and mathematical big ideas. About 500 tasks and questions that teachers can adapt or use as-is. Teaching tips and task variations. A template to help teachers build new tasks. "Look-fors" to see student thinking and diagnose difficulties. Guidance for using follow-up questions and math conversation to create a rich math classroom"
Includes bibliographical references and index.
Keywords: x; Individualized instruction; Effective teaching